Viruses Circulating in African Honey Bees in Uganda - Otim, Agnes S.; Kajobe, Robert; P’Odyek Abila, Patrick; Kasangaki, Patrice; Echodu, Richard (Bee World, 2019)
Worldwide, honey bees are hosts of more than 20 identified bee viruses (de Miranda, Gauthier, Ribiere, & Chen, 2011); most of them are single stranded RNA viruses belonging to order Picornavirales which has five families, two of which (Iflaviridae and Dicistroviridae) contain the common bee viruses (De Smet et al., 2012). Nine of these bee viruses on the African continent are reviewed by Pirk, Strauss, Yusuf, Démares, and Human (2016). The Acute Bee Paralysis Virus (ABPV), Israeli Acute Paralysis Virus (IAPV) and Black Queen Cell Virus (BQCV) were reported in South Africa (Strauss et al., 2013). In Kenya, Muli et al. (2014) detected ABPV, BQCV and Deformed Wing Virus (DWV). In Benin, Amakpe, De Smet, Brunain, and Ravoet (2015) reported Lake Sinai Virus (LSV), while Onyango et al. (2016) added to Kenya’s bee viruses the Varroa Destructor Virus-1 (VDV-1) and Kakugo Virus. Apis melifera Filamentous Virus (AmFV) in South Africa is reviewed by Allen and Ball (1996). In Uganda, Kajobe et al. (2010a) detected the BQCV and none of the samples screened in their study tested positive for Chronic Bee Paralysis Virus (CBPV), Sac Brood Virus (SBV), ABPV, DWV, IABP, nor Apis iridescent virus, AIV. Studies of Chemurot (2017) show presence of ABPV, SBV, DWV, LSV and BQCV in bee colonies in eastern and western agro-ecological zones (AEZs) of Uganda.
Keywords: Viruses; African Honey Bees; Uganda